Role of Liquid-Liquid Phase Transitions in Mechanism of Erythrocyte Protection During Cooling with CRIHBT-115 Cryopreservative Agent - Khodko , Oleksiy (Problems of Cryobiology and Cryomedicine, 2021)
The presence in the system of critical liquid-liquid phase transition (PT) by the mechanism, resulting in formation of dispersion system, namely high-concentrated emulsion, has been established here during cooling when using polarized light microscopy and fixation of critical opalescence phenomenon in erythrocyte concentrate with glycerol-containing cryopreservative agent, designed at the Central Research Institute of Haematology and Blood Transfusion (Russia) (CRIHBT-115 ). The studied cryobiological system displayed no signs of crystallization. A phase behaviour of cryopreservative and supernatant has been studied during cooling-warming cycle. Changes in the volume of cryopreservative and erythrocyte concentrate were comparatively and qualitatively evaluated during cooling. The mechanism of protective action of cryopreservation solution has been determined. The similarity between physical and chemical processes during cooling-warming of erythrocyte cytoplasm and garlic meristem cells (germinal plant tissue) when entering cold anabiosis has been established. Probl Cryobiol Cryomed 2021; 31(3): 236–248